2018
DOI: 10.1016/j.ijsu.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of monopolar cautery versus clips for staple line bleeding control in Roux-en-Y gastric bypass

Abstract: In laparoscopic Roux-en-Y gastric bypass, monopolar cauterization for SLBC can be used instead of clipping. It appears that monopolar cautery is a safe and effective approach for SLBC in laparoscopic Roux-en-Y gastric bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Suturing the stapler line is a long process, although it also depends on technical skill. In another study comparing monopolar cautery and clip application in RYGB, no difference was found between the two methods in terms of operation time, and it was thought that the smoke caused by cauterization prolongs the operation time 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Suturing the stapler line is a long process, although it also depends on technical skill. In another study comparing monopolar cautery and clip application in RYGB, no difference was found between the two methods in terms of operation time, and it was thought that the smoke caused by cauterization prolongs the operation time 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Control of staple line bleeding with bipolar cautery is a known method 3,4 . However, the number of studies on the use of monopolar cautery is very few 2,5 . To the best of our knowledge, there is no other study comparing monopolar cautery with continuous invaginating hand-sew suturing for SLBC after LSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for SLB control, monopolar cautery is not always recommended because it may weaken the staple line, although it is a simple and rapid method for reaching hemostasis. However, Gundogan et al recently investigated the e cacy of monopolar cautery versus clips for SLB control in RYGB [13]. Sağlam et al used only monopolar cautery for SLB control in 187 patients undergoing SG [14].…”
Section: Discussionmentioning
confidence: 99%